Non-neurotoxic activity of Malayan krait (Bungarus candidus) venom from Thailand - Charoenpitakchai, Mongkon; Wiwatwarayos, Kulachet; Jaisupa, Nattapon; Ahmad Rusmili, Muhamad Rusdi; Mangmool, Supachoke; Hodgson, Wayne C.; Ruangpratheep, Chetana; Chanhome, Lawan; Chaisakul, Janeyuth (Springer Nature, 2018)
Background Envenoming by kraits (genus Bungarus) is a medically significant issue in South Asia and Southeast Asia. Malayan krait (Bungarus candidus) venom is known to contain highly potent neurotoxins. In recent years, there have been reports on the non-neurotoxic activities of krait venom that include myotoxicity and nephrotoxicity. However, research on such non-neurotoxicity activities of Malayan krait venom is extremely limited. Thus, the aim of the present study was to determine the myotoxic, cytotoxic and nephrotoxic activities of B. candidus venoms from northeastern (BC-NE) and southern (BC-S) Thailand in experimentally envenomed rats.